Gender-related differences in survival in locally advanced luminal A breast cancer patients: Gender difference on luminal a breast cancer - Sanli, Ahmet Necati (Journal of Surgery and Medicine, 2025)
Background/Aim: Breast cancer is known to exhibit variations in clinical outcomes based on several factors, including molecular subtypes and patient demographics, yet the influence of gender on survival outcomes in patients with locally advanced stage luminal A breast cancer remains underexplored. This study aimed to determine how gender affects the survival of patients with locally advanced stage breast cancer. Methods: Data were obtained from the Surveillance Epidemiology and End Results (SEER) database. Patients with luminal A molecular subtype and locally advanced stage breast cancer who had been diagnosed between 2010 and 2019 were included in the study. Age, gender, marital status, race, and year of diagnosis were classified as clinical data, and tumor localization, laterality, grade, stage, surgical status, radiotherapy and chemotherapy status, cause of death, and survival time were classified as oncological data. Data were compared based on gender. Results: The study included a total of 46,730 patients. A very small percentage of the patients were male (1.2%), while 98.8% were female. Male patients were significantly older and had a higher marriage rate. Racial distribution differed slightly with more black patients among the males. Grade 2 tumors were most prevalent in both genders, but males had higher grade 3 tumors. Stage 3B and 3C tumors were more common in males, but no significant difference for Stage 3C based on gender was detected. Surgical rates were similar between genders, while females had higher rates of treatment with radiotherapy and chemotherapy. Females exhibited significantly higher overall survival rates (64.4% versus 52.2%). Cancer-specific survival did not differ significantly (76.3% versus 72.1%). Males had a 1.6 times higher overall mortality risk, which was reduced to 1.3 times after adjusting for other prognostic factors. Conclusion: No difference in cancer-specific survival between men and women with locally progressed luminal A breast cancer was found. These results highlight the significance of considering gender-specific characteristics while managing patients and predicting their prognosis. To fully understand the underlying mechanisms behind the survival differences between male and female patients, further studies are required.